PENGARUH IKLIM ORGANISASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PERAWAT PADA RSUD BANGKINANG - Lisa Irawan; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine how much the influence of organizational climate and work motivation on the job satisfaction. Samples in this study were taken as many as 52 respondent and in this study used a Simple Random Sampling. Using simple regression analysis and multiple regression analysis.The results of this study indicate that organizational climate has a significant on the job satisfaction. Work Motivation has a significant on the job satisfaction. And simultaneously organizational climate and work motivation have a significant effect on the job satisfaction. Future studies are suggested to use other methods in examping on the job satisfaction, for example through in depth interviews with respondent. Keywords : Organizational Climate, Work Motivation, Job Satisfaction